Multispectral imaging sensors for detecting UV endogenous and NIR exogenous fluorophores - Gruev V; Zhu Z; Jin Y; Hajek B; Kondov G; Kondov B; Bogdanovska Todorovska, Magdalena (SPIE Digital Library, 2024)
Lymph node mapping is a routine procedure during numerous cancer surgeries, yet the intraoperative identification of affected lymph nodes remains a clinical challenge. In response to this, we've introduced a multispectral camera that covers the UV, visible, and NIR spectrum. This innovative device facilitates lymph node imaging using both endogenious UV fluorescence and exogenious introduced NIR fluorescence, aiding in pinpointing the affected nodes. This presentation will showcase relevant clinical findings.